Komposisi dan Keanekaragaman Jenis Vegetasi pada Beberapa Tutupan Lahan di Taman Nasional Sebangau Kalimantan Tengah: Species Composition and Diversity of Vegetation In Several Land Covers in Sebangau National Park Central Kalimantan - Nisfiatul Hidayat; Orimanto, Orimanto; Yulianti, Reri; Nuwa, Nuwa; Yanarita, Yanarita; Fauzi, Fouad (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2024)
The study aims to determine the composition and diversity of species in several covers, namely: swamp, secondary swamp forest, swamp shrubs and swamps in the Sebangau National Park area. The number of plant species found in the three forest communities in the study site was 62 species. The most dominant plant species at almost all growth levels was Tumih (Combretocarpus rotundatus), followed by guava (Syzgium sp.), and Tamehas (Memecylon costatum). Meranti (Shorea sp.) and piais (Nephelium lappaceum L.) species were dominant in the secondary swamp forest community. The species diversity index with a range of1.24-3.32 and species richness index with a range of 2.63-6.42 in the three types of land cover is classified as medium to high. The evenness index is classified as high for all growth stages, except for the seedling level in the swamp shrub community which is classified as medium.